2019
DOI: 10.1002/app.47699
|View full text |Cite
|
Sign up to set email alerts
|

PBAT/TPS‐nanowhiskers blends preparation and application as food packaging

Abstract: About 85–90% of the market for new materials in biodegradable packaging is served by various blends and composites containing starch in some portion. In an attempt to satisfy the increasing consumer demand, innovative materials are being developed. This includes the concept of active packaging, which, in addition to protecting, interacts with the packaged product. In this context, flexible films have been prepared from blends of poly(butylene adipate‐co‐terephthalate), thermoplastic starch (TPS), and cellulose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…Initially, cellulose was extracted from sisal fibers according to the procedure described by Silva et al . Acid hydrolysis was performed using sulfuric acid (64% w w −1 ) for both cellulose sources: sisal and commercial microcrystalline cellulose.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, cellulose was extracted from sisal fibers according to the procedure described by Silva et al . Acid hydrolysis was performed using sulfuric acid (64% w w −1 ) for both cellulose sources: sisal and commercial microcrystalline cellulose.…”
Section: Methodsmentioning
confidence: 99%
“…The morphologies of the nanoparticles were determined via Transmission Electron Microscopy (TEM) (Jeol, JEM‐1230, Iowa City, Iowa), according to the methodology proposed by Silva et al . One drop of an aqueous suspension (0.3% w v −1 ) containing the nanoparticles was deposited on a nickel grid (200 mesh).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While PBAT is of petrochemical origin, it is biodegradable, and it was found that the blends of TPS and PBAT also have improved mechanical and rheological properties [241]. In addition, when cellulose nanowhiskers (CNW) were included in PBAT/TPS blends, morphological and water barrier properties of the films were improved, and the films exhibited antioxidant and antimicrobial activities [242].…”
Section: Starchmentioning
confidence: 99%
“…It is also possible to observe the presence of micropores in the studied formulations (Figure (a,b)—40× magnification), and these formations can strongly interfere with the barrier properties and the mechanical behavior, and consequently, the stability of the packaged product. Recently, flexible films have been prepared from blends of PBAT, thermoplastic starch, and cellulose nanocrystals at different concentrations (0–3.0 wt %) and with distinct compatibilizing agents (glycerol, stearic acid, and citric acid) by flat extrusion . The micrographs obtained by the authors showed the films with very porous surface as a function of the nanocrystals concentration.…”
Section: Resultsmentioning
confidence: 99%